An Evaluation of Bidirectional Converter Topologies for Ups Applications - Baldwin Immanuel, T; Muthukumar, P; Rajavelan, M; Gnanavel, C; Veeramuthulingam, N (International Journal of Engineering and Technology, 2018)
This paper emphases on different four topologies of Non-Isolated Bidirectional converter which are being equated for its suitability in the application of UPS. The evaluation is based on efficiency, number of switches and voltage gain used in the converter. The working philosophies and design equations of topologies are discuss in detail. The comparative studies and simulation results are deliberated for Boost mode. All the topologies of the low voltage side and high voltage sideÂ are connected with 24V battery and 260V DC bus with switching frequency 30 kHz.Â Â